2012
DOI: 10.1029/2012ja017708
|View full text |Cite
|
Sign up to set email alerts
|

PENGUIn/AGO and THEMIS conjugate observations of whistler mode chorus waves in the dayside uniform zone under steady solar wind and quiet geomagnetic conditions

Abstract: [1] We perform a case study of conjugate observations of whistler mode chorus waves on the dayside made on 26 July 2008 by three THEMIS spacecraft and ground-based ELF/ VLF receivers at the Automatic Geophysical Observatories (AGO) in Antarctica supported by the U.S. Polar Experiment Network for Geospace Upper-atmosphere Investigations (PENGUIn) project. The dayside chorus waves were excited during a period of no substorm activity with geomagnetic indices indicating quiet conditions (Dst $ À10 nT; AE < 200 nT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 120 publications
2
47
0
Order By: Relevance
“…Previously, Zhou et al () have shown that chorus waves at the dayside magnetosphere are excited after the IP shock arrival. The IP shock impinging on the magnetosphere leads to a more homogeneous background magnetic field configurations in the near‐equatorial dayside magnetosphere and therefore lower the threshold of nonlinear chorus wave growth, favoring chorus wave generation (Keika et al, ; Tao et al, ). This is supported by the observational evidence that a decrease of solar wind dynamic pressure causes an increase of the threshold for chorus wave excitation and thus results in disappearance of plasmaspheric hiss and exohiss (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Zhou et al () have shown that chorus waves at the dayside magnetosphere are excited after the IP shock arrival. The IP shock impinging on the magnetosphere leads to a more homogeneous background magnetic field configurations in the near‐equatorial dayside magnetosphere and therefore lower the threshold of nonlinear chorus wave growth, favoring chorus wave generation (Keika et al, ; Tao et al, ). This is supported by the observational evidence that a decrease of solar wind dynamic pressure causes an increase of the threshold for chorus wave excitation and thus results in disappearance of plasmaspheric hiss and exohiss (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They are stronger during the times when geomagnetic activity is enhanced [ Tsurutani and Smith , ; Meredith et al ., ; Miyoshi et al ., ; Li et al ., ]. On the dayside, chorus waves are associated with drift shell splitting effect caused by day‐night asymmetry of the magnetosphere due to solar wind compression [ Gail and Inan , ; Gail et al ., ; Salvati et al ., ; Fu et al ., ; Keika et al ., ] and show little dependence of occurrence on geomagnetic activity [ Tsurutani and Smith , ; Spasojevic and Inan , ].…”
Section: Introductionmentioning
confidence: 99%
“…Under the ideal magnetohydrodynamic condition, the density should vary in phase with the magnetic field. For the chorus generated at the equator, both theoretical (Katoh & Omura, 2013;Katoh et al, 2018;Omura et al, 2008) and observational (Keika et al, 2012; studies have suggested that the spatial inhomogeneity of the background magnetic field can control the adiabatic force on the resonant electrons and then affect the nonlinear growth process. For the hot electrons with the cyclotron, bounce, and drift frequencies substantially deviating from the observed toroidal wave frequency, their adiabatic oscillations are ignorable corresponding to the tiny (<1%) oscillation of the toroidal ULF magnetic field (Figure 4).…”
Section: Discussionmentioning
confidence: 99%